Prolonged stimulation of β2-adrenergic receptor with β2-agonists impairs insulin actions in H9c2 cells - Warisara Parichatikanond; Akiyuki Nishimura; Motohiro Nishida; Supachoke Mangmool (Elsevier, 2018)
Insulin resistance is a condition in which there is a defect in insulin actions to induce glucose uptake into the cells. Overstimulation of β2-adrenergic receptors (β2ARs) is associated with the pathogenesis of insulin resistance in the heart. However, the mechanisms by which β2-agonists affect insulin resistance in the heart are incompletely understood. The β2-agonists are used for treatment of asthma due to bronchodilating effects. We also investigated the effects of β2-agonists in human bronchial smooth muscle (HBSM) cells. In this study, we demonstrate that chronic treatment with salbutamol, salmeterol, and formoterol inhibited insulin-induced glucose uptake and GLUT4 synthesis in H9c2 myoblast cells. Sustained β2AR stimulation also attenuated GLUT4 translocation to the plasma membrane, whereas short-term stimulation had no effect. In HBSM cells, prolonged treatment with β2-agonists had no effect on insulin-induced glucose uptake and did not alter insulin-induced expressions of GLUT1, GLUT4, and GLUT10. In addition, genetic polymorphisms at amino acid positions 16 and 27 of β2AR are linked to insulin resistance by significant suppression of GLUT4 translocation compared to wild-type. Thus, prolonged β2AR stimulation by β2-agonists impairs insulin actions through suppression of GLUT synthesis and translocation only in H9c2 cells. Keywords: β2AR polymorphism, β2-Agonist, GLUT translocation, Glucose uptake, Insulin resistance